الحكم الأخلاقى وعلاقته بمستوى التفاؤل والتشاؤم لدى طلبة جامعة اليرموك - مصطفى، منار; مقالده، تامر أحمد حسن (جامعة اليرموك - عمادة البحث العلمي, 2014)
هدفت الدراسة إلى معرفة مستوى الحكم الأخلاقي ومستوى التفاؤل والتشاؤم لدى طلبة جامعة اليرموك، والتعرف على العلاقة بين الحكم الأخلاقي والتفاؤل والتشاؤم، والفروق ذات الدلالة الإحصائية (a = 0.05) في مستويات الحكم الأخلاقي والتفاؤل والتشاؤم، التي يمكن أن تعزى إلى كل من: الجنس، والتخصص. تكونت عينة الدراسة من (500) طالب وطالبة من جامعة اليرموك تم اختيارهم في الفصل الدراسي الثاني للعام 2012-2013م. ولتحقيق أهداف الدراسة تم استخدام مقياس الحكم الأخلاقي للراشدين والمعد من قبل عبد الفتاح (2001)، كما تم تطوير مقياس التفاؤل والتشاؤم من قبل الباحثين لأغراض هذه الدراسة. أظهرت النتائج أن مستوى الحكم الأخلاقي جاء بدرجة متوسطة لدى طلبة جامعة اليرموك، وفي المرحلة الرابعة وهي: (التمسك الصارم بالقوانين والأنظمة) من مراحل الحكم الأخلاقي الستة عند كولبرج kohlberg، وأظهرت نتائج الدراسة مستوى مرتفعا من التفاؤل لدى طلبة جامعة اليرموك، كما أشارت نتائج الدراسة إلى وجود ارتباط إيجابي دال إحصائيا بين الحكم الأخلاقي والتفاؤل والتشاؤم على الدرجة الكلية للمقياس. كما أشارت نتائج الدراسة إلى وجود فروق دالة إحصائيا في مستوى الحكم الأخلاقي يعزى لمتغير الجنس، كانت الفروق لصالح الإناث. كذلك وجود فروق دالة إحصائيا في مستوى الحكم الأخلاقي تعزى لمتغير التخصص، ولصالح تخصص الكليات الإنسانية. وعدم وجود فروق دالة إحصائيا في مستوى التفاؤل والتشاؤم لدى طلبة جامعة اليرموك تعزى لأثر الجنس، أو التخصص. The study aimed to identify the moral judgment, optimism and pessimism level, among Yarmouk University students, as well as to reveal the relationship between moral judgment, optimism and pessimism, and the statistical significant differences (α =0.05) in the levels of moral judgment, optimism and pessimism, by gender and specialization variables. The study sample consisted of (500) Yarmouk University students selected in the second semester of 2012-2013 Academic year. To achieve the objectives of the study, the moral judgment scale for adults prepared by Abed Al-Fattah (2001) was used. Also, the researchers developed a scale to measure optimism and pessimism among students. The results showed a moderate degree of moral judgment in the fourth stage (strict adherence to laws and regulations) of the sixth Kohlberg's stages of moral judgment. The results also showed a high level of optimism among Yarmouk University students, The results of the study indicated that there was a statistically significant positive correlation between the moral judgment level and the domain of optimism and pessimism scale as whole among Yarmouk University students. The results of the study also indicated that there were statistically significant differences (α=0.05) in the moral judgment levels according to gender, in favor of females. There were statistically significant differences (α=0.05) in the moral judgment levels according to specialization variable, in favor of humanistic specialization colleges. In addition, there were no statistically significant differences in the levels of optimism and pessimism according to gender and specialization variables.
776374 685768 814188
Keywords: الحكم الأخلاقى -- التفاؤل والتساؤم لدى طلبة جامعة اليرموك